β-Cyclodextrin-based Polymers coating Magnetic Nanoparticles for Amitraz capture and detoxification: A biocompatible and scalable approach - Melo-Hurtado, F; Donoso-Gonzalez, O (ELSEVIER IRELAND LTD, 2025)
Sin Resumen Disponible